Reproductive Parameters of Female Long-finned Pilot Whales (Globicephala melas edwardii) from the Southwestern Atlantic - Soto, Florencia Anabella; Grandi, Maria Florencia; Garcia, Nestor Anibal; Crespo, Enrique Alberto; Dans, Silvana Laura
Mass strandings represent a valuable source of information, especially when it comes to difficult-to-access pelagic species, such as Globicephala melas edwardii. We collected reproductive organs from 27 female pilot whales stranded in Caleta Malaspina, Chubut, Argentina. Our main objective was to analyze reproductive parameters of female long-finned pilot whales in the southern hemisphere. To achieve this, we studied age and reproductive status in order to approximate age and body length at sexual maturity, breeding interval, and fertility of this subspecies. The maturity state was determined by recording different ovulation bodies obtained from histological sections and by assessing the presence of milk in the mammary glands and a fetus, and we concluded that 5 of the females were immature and 22 were mature females. Finding mature females in different reproductive states (resting, in lactation, pregnant, or pregnant and in lactation) along with the great variety of fetus sizes would indicate that copulation and birth are not governed by seasonality. Age at sexual maturity was 8 years old and length at sexual maturity would reach 365.50 cm. The annual pregnancy rate was constant with age for mature females at 0.41 ovul / year, with a breeding interval of 2.4 years. The average fertility varied between 0.19 and 0.21. All the parameters are within the estimated range for females of the North Atlantic subpopulation, except for the breeding interval, which was significantly lower than estimates for the northern subspecies. This study could be limited because all individuals come from a single mass stranding. While this study allowed us to reach some conclusions about the reproductive biology of female G. melas edwardii in the Southwestern Atlantic Ocean, further studies are needed to fully comprehend the behavior and biology of this species Fil: Soto, Florencia Anabella. Universidad Nacional del Comahue. Centro Regional Universitario Bariloche; Argentina. Consejo Nacional de Investigaciones Científicas y ...